THE INFLUENCE OF LEVERAGE, COMPANY SIZE, FREE CASH FLOW ON PROFIT MANAGEMENT OF IDX-LISTED MANUFACTURING COMPANIES: PENGARUH LEVERAGE, UKURAN PERUSAHAAN, FREE CASH FLOW TERHADAP MANAJEMEN LABA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Andrie Wiyogo; Ati Sumiati; Sri Zulaihati; Dwi Kismayanti Respati (Yayasan Education and Social Center, 2021)
This research aims to determine the effect of Leverage, Firm Size, and Free Cash Flow on Earnings Management. The data collection method used is the Study Documentation method. The affordable collection in this study was manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019 with 190 companies. Data collection by collecting data on the annual financial report on Indonesia Stock Exchange (IDX) web. The sample used was as many as 128 companies using random sampling techniques. The data analysis techniques used are multiple linear regression analysis, descriptive statistics analysis, pre-requirement, classic assumption, and hypothesis testing. Multiple linear regression analysis indicates that variables have a relation. Descriptive statistics analysis indicates an overview of each variable. Pre-requirement test analysis indicates data is distributed normally. Classic assumption test indicates data acceptable. Moreover, the hypothesis test result concludes that all hypotheses are acceptable. Based on the analysis, it is shown that leverage harms earnings management. Firm size has a positive effect on earnings management. Moreover, free cash flow harms earnings management. Then the coefficient determination in this study was 12,4% which showed the ability of leverage, firm size and free cash flow influencing earnings management while the rest were influenced by other factors not examined.